Global Increases in Lethal Compound Heat Stress: Hydrological Drought Hazards Under Climate Change. Issue 18 (24th September 2022) - Yin, Jiabo; Slater, Louise; Gu, Lei; Liao, Zhen; Guo, Shenglian; Gentine, Pierre
Abstract: Previous studies seldom consider humidity when examining heat‐related extremes, and none have explored the effects of humidity on concurrent extremes of high heat stress and low river streamflow. Here, we present the first global picture of projected changes in compound lethal heat stress ( T h )‐drought hazards (CHD) across 11, 637 catchments. Our observational datasets show that atmospheric conditions (e.g., energy and vapor flux) play an important role in constraining the heat extremes, and that T h (32% ± 11%) yields a higher coincidence rate of global CHD than wet‐bulb temperature (28% ± 11%), driven by lower relative humidity (RH) and thus air dryness in T h extremes. Our large model ensemble projects a 10‐fold intensification of bivariate CHD risks by 2071–2100, mainly driven by increases in heat extremes. Future declines in RH, wind, snow, and precipitation in many regions are likely to exacerbate such water and weather‐related hazards (e.g., drought and CHD). Plain Language Summary: Water and weather‐related extremes such as droughts and heatwaves typically occur simultaneously, posing larger risks to humans and ecosystem than any individual hazard. Extreme high lethal heat stress, which is governed by both temperature and humidity, inhibits the evaporative cooling function of the human body. However, changes in lethal heat stress under past and future climate are poorly understood at the global scale, and no study has yet explored their influences on the risk of compound heat stress‐drought events. Here, we provide the first global picture of the concurrent high heat stress–low streamflow extremes and their projected changes. The fraction of lethal heat extremes accompanied by drought hazards is projected to rise markedly throughout the 21st century. The global magnitude and occurrence of compound hazards is projected to intensify by 4–10 times by 2071–2100, mainly due to the increasing severity of heat extremes. Our study reveals an increasing global risk of compounding hazards, highlighting the need to better prepare adaptation and mitigation solutions in the Anthropocene. Key Points: We present the first global assessment of compound extremes of high lethal heat stress and low river streamflow Lethal heat stress yields a higher coincidence rate of compound hazards than wet‐bulb temperature Future lethal heat stress‐drought events are mainly exacerbated by changes in heat extremes